1999
DOI: 10.1073/pnas.96.24.13777
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Ser-20 mediates stabilization of human p53 in response to DNA damage

Abstract: Stabilization of p53 in response to DNA damage is caused by its dissociation from Mdm2, a protein that targets p53 for degradation in the proteasome. Dissociation of p53 from Mdm2 could be caused by DNA damage-induced p53 posttranslational modifications. The ATM and ATR kinases, whose activation in response to ionizing radiation (IR) and UV light, respectively, is required for p53 stabilization, directly phosphorylate p53 on Ser-15. However, phosphorylation of Ser-15 is critical for the apoptotic activity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
423
3
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(452 citation statements)
references
References 57 publications
(111 reference statements)
20
423
3
6
Order By: Relevance
“…Most of the p53 is degraded via the ubiquitin-dependent proteasome pathway, and thus it is interesting to determine how the p53 activation signals (DNA damage) affect this process of degradation. The phosphorylation of p53 in Ser20 activates p53 as a transcription factor and mediates its cellular stabilization in response to DNA damage (Appella and Anderson 2001;Chehab et al 1999;Ashcroft et al 2000). Thus, we have observed that during the postprandial period, the intake of the Med +CoQ diet induced a decrease in p53 protein phosphorylated at Ser20, probably due to a decrease in the signals that trigger this phosphorylationespecially DNA damage-as it can be corroborated by the reduced levels of 8-OHdG observed in this Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Most of the p53 is degraded via the ubiquitin-dependent proteasome pathway, and thus it is interesting to determine how the p53 activation signals (DNA damage) affect this process of degradation. The phosphorylation of p53 in Ser20 activates p53 as a transcription factor and mediates its cellular stabilization in response to DNA damage (Appella and Anderson 2001;Chehab et al 1999;Ashcroft et al 2000). Thus, we have observed that during the postprandial period, the intake of the Med +CoQ diet induced a decrease in p53 protein phosphorylated at Ser20, probably due to a decrease in the signals that trigger this phosphorylationespecially DNA damage-as it can be corroborated by the reduced levels of 8-OHdG observed in this Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, its phosphorylation inhibits the binding between p53 and Mdm2. Mdm2 is a protein with E3 ligase activity whose function is to ubiquitinate p53, and serves to degrade the protein when not needed (Chehab et al 1999;Brooks and Gu 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many serine residues within the N-and C-terminal regions of p53 are phosphorylated in response to stress conditions such as hypoxia and DNA damage (Kruse and Gu, 2009). Both Ser20 and Ser37 phosphorylation on the p53 protein has been shown to have an important role in p53 stability and downstream apoptotic function (Chehnab et al, 1999;Unger et al, 1999;Li et al, 2006;Amano et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…DNA is shown as linear fragment with four white arrows within representing p53 RE made of four head-to-head arranged pentamers the N-terminus of p53 is extensively modified. Site-specific phosphorylation of the TA domain is important for both, p53 stability 82,83 and activity 50,[84][85][86][87] and has been shown to be interdependent. 88 There are also qualitative differences in phosphorylation in response to different genotoxic agents.…”
Section: The Complexity Of the P53 Transactivation Domainmentioning
confidence: 99%